THE INFLUENCE OF WORK PROGRAMS, ORGANIZATIONAL CULTURE, AND LEADERSHIP ON GOLKAR PERFORMANCE - Sari, Irma Mayang; Suhartono, Suhartono; Qodariah, Qodariah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to analyze the influence of work programs, organizational culture, and leadership on the performance of the Golkar. In ever-changing politics, political parties need effective work programs, strong organizational culture, and quality leadership to improve organizational performance. The population of this study was all Golkar cadres at the central and regional levels, with samples taken proportionally from various levels of party cadres using the purposive sampling method, and the number of samples was 105 respondents calculated using the Cochran formula. Data were collected through a questionnaire with a Likert scale to obtain cadre perceptions of the effectiveness of work programs, organizational culture, leadership, and party performance. The data analysis technique used was Structural Equation Modeling (SEM) with the help of SmartPLS software. The results showed that work programs, organizational culture, and leadership had a significant influence on party performance.